Improving productivity of maize-lentil rotation in alkaline Fluvisol following soil test crop response (STCR) - targeted yield approach of nutrient management. Issue 7 (7th June 2022) - Venkatesh, Madasur Subbabhat; Hazra, Kali Krishna; Ghosh, Probir Kumar; Singh, Kranti Kumar
ABSTRACT: Soil-test crop response (STCR) approach is aiming to precise adjustment of fertilizers under varying soil-test values for targeted-yield, presently gaining recognitions for sustainable nutrient management. The study aimed to envisage the precision scale of STCR targeted-yield models in maize-lentil rotation in alkaline Fluvisol under sole-fertilizer and integrated nutrient management (with farmyard manure). Fertility-gradient, test-crop diagnostic, and validation trials were conducted following STCR technical program. Soil fertility gradient and variable fertilizer doses had caused a large variation in grain yield of maize (0.99–4.94 t ha −1, CV = 30%) and lentil (1.11–2.02 t ha −1, CV = 13%). Lentil had increased potential to utilize soil nutrient pools; in contrast, maize was highly responsive to fertlizer nutrients. Multivariate-regression analysis revealed that fertilizers N, P, and S had a strong and direct influence on maize yield; where fertilizer-P was the primary yield-determining variable for lentil. Both sole-fertilizer and integrated STCR-based treatments attained the targeted-yields in maize. However, STCR treatments could not attain the targeted-yields in lentil (17–29% deviation), but had yield advantage over the blanket recommended fertilizer dose. Hence, in tropical-alkaline soils, integrated STCR targeted-yield approach could be the sustainable nutrient management option(s) for improving the productivity of the maize-lentil system.